Dysfunction in atox-1 and ceruloplasmin alters labile Cu levels and consequently Cu homeostasis in C. elegans - Weishaupt, Ann-Kathrin; Lamann, Karsten; Tallarek, Elke; Pezacki, Aidan T.; Matier, Carson D.; Schwerdtle, Tanja; Aschner, Michael; Chang, Christopher J.; Stürzenbaum, Stephen R.; Bornhorst, Julia (Frontiers in Molecular Biosciences, 2024)
Copper (Cu) is an essential trace element, however an excess is toxic due to its redox properties. Cu homeostasis therefore needs to be tightly regulated via cellular transporters, storage proteins and exporters. An imbalance in Cu homeostasis has been associated with neurodegenerative disorders such as Wilson's disease, but also Alzheimer's or Parkinson's disease. In our current study, we explored the utility of using Caenorhabditis elegans (C. elegans) as a model of Cu dyshomeostasis. The application of excess Cu dosing and the use of mutants lacking the intracellular Cu chaperone atox-1 and major Cu storage protein ceruloplasmin facilitated the assessment of Cu status, functional markers including total Cu levels, labile Cu levels, Cu distribution and the gene expression of homeostasis-related genes. Our data revealed a decrease in total Cu uptake but an increase in labile Cu levels due to genetic dysfunction, as well as altered gene expression levels of Cu homeostasisassociated genes. In addition, the data uncovered the role ceruloplasmin and atox-1 play in the worm's Cu homeostasis. This study provides insights into suitable functional Cu markers and Cu homeostasis in C. elegans, with a focus on labile Cu levels, a promising marker of Cu misregulation during disease progression.